OPTIMALISASI PENGELOLAAN EKOSISTEM DALAM STRATEGI PEMBANGUNAN KABUPATEN SLEMAN: SEBUAH TINJAUAN LITERATUR SISTEMATIS - Fikri Danang Himawan; Fathur Khoirul Arifin; Pramudya Bumishambara (Badan Perencanaan Pembangunan Daerah Kabupaten Sleman, 2026)
Sleman Regency, situated on the southern slopes of Mount Merapi within Yogyakarta's rapidly urbanizing peri-urban corridor, confronts accelerating agricultural land conversion driven by intensifying development pressures. No systematic cross-disciplinary synthesis has integrated existing findings into a coherent evidence base for ecosystem-based regional development planning. This study conducted a Systematic Literature Review (SLR) following PRISMA 2020 protocols on Scopus, yielding 27 final articles. Narrative thematic synthesis revealed four principal themes: (1) agricultural land conversion and spatial planning under disaster-risk contexts; (2) food security and the transition toward sustainable farming systems; (3) ecosystem integrity and ecological vulnerability; and (4) rural tourism and multi-actor governance. Five evidence-based policy strategies are proposed: strengthening organic farming zones with spatial regulatory instruments, establishing ecosystem service payment schemes linked to Merapi watershed governance, scaling community-based tourism within an integrated landscape framework, institutionalizing multi-stakeholder governance platforms, and deploying gender-responsive food security programs. These findings furnish an empirical foundation for more integrated, ecosystem-centred regional development planning in Sleman.